Estudio de factibilidad para la implementación de una línea de productos (pulpa de frutas) en la microempresa Asopruv ubicada en la provincia de Cotopaxi, cantón Salcedo, parroquia Panzaleo, barrio Pataín en el período 2014 - 2015 - Acaro Sarabia, Sabrina Alejandra (2016)
It is a set in four major areas of study which are the market research, technical studies, organizational studies, and economic study - financial. The market study we establish the quantitative and qualitative characteristics of the potential users, to get information, surveys were conducted with a sample of consumers. The results were as follows: in regards to the consumption of fruit pulps the results show that 68% (260 people) consume fruit pulp, while 32% (123 people) do not consume, 53% (203 people) acquire fruit pulp considering the quality, 26% (100 people ) buy the product based on price, and according to how often they buy fruit pulps have a higher proportion weekly at a rate of 44% (169 people), while 31% purchase the product daily (119 people). These results of this study show that the product will have a high demand when brought to the market. In the economic study – financial, the following results were obtained through the financial indicators such as IRR and NPV, thus we determined the NPV is $ 12,146.56 which shows that the NPV is lower than the investment. As such, although the project is not profitable in the first two years of implementation it does have the IRR of 38% that is greater than zero and is greater than 4.76 TMAR. Therefore, the project is viable and profitable.